1923. OPAT or No-PAT? Evaluation of Outpatient Parenteral Antimicrobial Therapy (OPAT) Patients Receiving Daptomycin or Ertapenem for "Ease of Administration". (26th November 2018) - Britt, Rachel S; Lasalvia, Mary T; Padival, Simi; Patel, Parth V; McCoy, Christopher; Mahoney, Monica V
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) allows for long-course intravenous treatment of infections without lengthy hospital stays. Upon discharge, antimicrobial therapy may be broadened to ertapenem or daptomycin for "ease" of once-daily administration. Patients requiring subsequent readmission should be properly tailored to pre-OPAT regimens to minimize collateral damage and reduce cost. This study assessed the continuation of "ease of administration (EOA) regimens" upon hospital readmission during or immediately following OPAT. Methods: This was a single-center, retrospective review of adult patients enrolled in OPAT and discharged between January 1, 2014 and September 30, 2017 on ertapenem or daptomycin for "EOA." This was defined by the presence of the terms "convenience" or "EOA" in OPAT notes or by broadening of coverage to ertapenem or daptomycin upon OPAT enrollment despite adequate therapy with more narrow-spectrum agents. Patients receiving directed carbapenem or daptomycin therapy prior to OPAT enrollment were excluded. The primary outcome was the percentage of patients readmitted during or within 90 days of their OPAT course and maintained on an "EOA regimen" of antibiotics. Secondary outcomes included inpatient therapy cost, rates of Clostridium difficile infection, and adverse drug reactions. Demographics and outcomes were summarized using descriptive statistics. Results: Of the 188 patients receiving an OPAT "EOA regimen, " 71 were readmitted, representing 113 unique readmissions. Patients were mostly male (81%) with a median age of 57 years. "EOA regimens" were continued in 27% of hospital readmissions. The Infectious Diseases team was consulted in 48% of cases, and the Antimicrobial Stewardship Team intervened in 26%, prompting de-escalation in a total of 28% of cases. C. difficile infections and adverse events occurred in 7% and 12% of readmissions respectively. The median drug acquisition cost of inpatient "EOA regimens" was $121 per readmission. Conclusion: At our institution, OPAT "EOA regimens" were continued in 27% of hospital readmissions indicating a role for improved indication documentation and antimicrobial stewardship involvement. Disclosures: C. McCoy, Merck Inc.: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. M. V. Mahoney, Melinta Therapeutics: Consultant, Consulting fee. Cutis Pharma: Consultant, Consulting fee. Tetraphase Pharmaceuticals, Inc.: Consultant, Consulting fee. Roche Diagnostics USA: Consultant, Consulting fee.